2005
DOI: 10.1136/adc.2004.049536
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of thyroid function in Down's syndrome in the first two decades

Abstract: Aims and Methods: Thyroid function tests were initially carried out on 122 children with Down's syndrome aged 6-14 years and then repeated four to six years later in 103 adolescents (85% of the group of 122) when they were aged 10-20 years (median 14.4 years). At the second test two were hypothyroid and two with isolated raised thyroid stimulating hormone (IR-TSH) were receiving thyroxine. Results: At the first test there were 98 (80%) euthyroid children: 83 were retested and four (5%) had IR-TSH. At the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 20 publications
5
83
1
9
Order By: Relevance
“…23 Gibson PA et al also observed that 47% of subclinical hypothyroid Down's syndrome patients were subsequently found to have normal TSH levels after a gap of four to six years. 24 We do not know whether our cases are transient type or not, as we could not follow up the enrolled cases.…”
Section: Discussionmentioning
confidence: 99%
“…23 Gibson PA et al also observed that 47% of subclinical hypothyroid Down's syndrome patients were subsequently found to have normal TSH levels after a gap of four to six years. 24 We do not know whether our cases are transient type or not, as we could not follow up the enrolled cases.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, of uncertain etiology, can be referred to as subclinical hypothyroidism (SH) and seems usually to be transitory and self-limiting without treatment (9,10). However, there are few systematic studies on SH, and the factors related to its remission are unclear.…”
Section: T He Prevalence Of Medical Conditions In Individuals Withmentioning
confidence: 99%
“…Blood samples were taken from 30 nondiabetic schoolaged children with Down's syndrome (15 male and 15 female, 4 -21 years of age) during routine thyroid screening in the area covered by the Gloucestershire Health Authority, U.K. Aliquots of DNA samples from 83 children with Down's syndrome had been collected as part of a study of congenital heart disease in Down's syndrome (15). Samples were also available (109 DNA and 106 serum) for analysis from a population-based study of children with Down's syndrome in Manchester, the Hester Adrian Research Centre cohort (16). There was no clinical evidence of diabetes in any of these children.…”
Section: Methodsmentioning
confidence: 99%